(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Electro chemical discharge machining (ECDM) is a hybrid process which combines the features of electro chemical machining (ECM) and electro discharge machining (EDM).The need for micromachining of advanced engineering materials started increase in demand in various sectors like nuclear, aerospace and medical industries. Electrochemical discharge machining (ECDM) technique is that involves high-temperature melting and accelerated chemical etching under the high electrical energy discharged and has potential to machine electrically non-conductive materials such as glass, quartz, composite, ceramics. In ECDM, gas film and sparks are generated on a tool when voltage is applied between the tool and a counter electrode. Work-piece materials are removed mainly by the heat of the sparks. The spark generation is affected by both the voltage and electrolyte conditions. In this present work, The effect of process variables such as electrolyte concentration (EC), duty factor (DF), voltage (V), on response parameters such as Material Removal Rate (MRR), Tool Wear Rate (TWR), Diametric overcut (DOC) have been investigated sodalime glass in electrochemical discharge machining (ECDM) using tungsten carbide electrode. Analysis of variance (ANOVA) and F-test were performed to determine the significant parameters at a 95% confidence interval.